Seasonal fluctuations in the price of natural rubber in India - Ipe C V (Indian Journal of Natural Rubber Research, 1988)
The paper analyses the seasonal variations in rubber prices. The analysis showed that the seasonal index was the highese in July and the lowest in December. Production of rubber showed marked seasonality. The analysis of price in relation to productioin and consumption showed that seasonality in prriaces was not much pronounced during months in which production change was predominant, which in turn point to the possibility of oligopsony in the buying market. During the peak production period, consumption was found to fall resulting in low prices. This necissitates the need for buffer stock operations so as to buy and store excess supplies and hold them off the market in times of falling prices and release them when the prices rise. The producer is benefited by stabilisation of his income and the manufacturer through an assured supply of raw material.
Keywords: Natural Rubber Consumption; Natural Rubber Consumption; Natural Rubber Prices; Natural Rubber Prices; Natural Rubber Production; Natural Rubber Production; Natural Rubber Stock; Natural Rubber Stock; Oligopsony; Oligopsony; Seasonal Fluctuations in Rubber Prices; Seasonal Fluctuations in Rubber Prices